2018
DOI: 10.1186/s12864-018-4587-z
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome profiling of genes related to light-induced anthocyanin biosynthesis in eggplant (Solanum melongena L.) before purple color becomes evident

Abstract: BackgroundThe anthocyanins are highly enriched in eggplants (Solanum melongena L.) with purple peel. However, our previous study showed that anthocyanins biosynthesis in eggplant cultivar ‘Lanshan Hexian’ was completely regulated by light and color becomes evident at most 2 days after exposure to light. In the present investigation, transcriptome study was made to explore the underlying molecular mechanisms of light-induced anthocyanin biosynthesis in eggplant (Solanum melongena L.) before color becomes eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 91 publications
1
39
0
Order By: Relevance
“…It has been revealed that R2R3-MYB and bHLH transcription factors, together with WDR proteins play an important role in regulating the transcription of structural genes of anthocyanin biosynthesis [2,4,6,12] . In eggplant, SmMYB1 and SmMyb C was found to have higher transcript levels in violet eggplant compared to white eggplant fruits [4] .…”
Section: Regulatory Genes Involved In Anthocyanin Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been revealed that R2R3-MYB and bHLH transcription factors, together with WDR proteins play an important role in regulating the transcription of structural genes of anthocyanin biosynthesis [2,4,6,12] . In eggplant, SmMYB1 and SmMyb C was found to have higher transcript levels in violet eggplant compared to white eggplant fruits [4] .…”
Section: Regulatory Genes Involved In Anthocyanin Biosynthesismentioning
confidence: 99%
“…The fruit skin color of eggplant ranges from white to dark purple, and is one of the primary exterior quality and economic characteristics. Although there is a big diversity of eggplant varieties varying in shape and color, the dark purple type receive more attention for high levels of anthocyanin accumulation [2] . A broad spectrum of color intensity exists within the group of dark purple colored cultivars, but intensive, uniform and lasting fruit color types are most preferred by consumers than the paler types, especially in China [3] .…”
Section: Introductionmentioning
confidence: 99%
“…After publication of the original article [ 1 ] it was noted that in Additional file 1: Table S1, and Fig. 1, specific primer sequences were incorrect, and taken from Sme2.5_02154.1_g00001.1 rather than Sme2.5_13923.1_g00001.1.…”
Section: Correctionmentioning
confidence: 99%
“…Furthermore, anthocyanin biosynthesis of eggplants is reportedly affected by several environmental factors, such as light (Li et al 2018;Li et al 2017). The RNA-seq results showed that the 11 abovementioned anthocyanin biosynthesis structure genes were upregulated during light-induced anthocyanin biosynthesis in eggplants (Li et al 2018;Li et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of SmMYB1 resulted in the significant accumulation of anthocyanin, with most anthocyanin structural genes being dramatically upregulated (Zhang et al 2016b). A recent study suggested that light can positively regulate the anthocyanin structural genes and the R2R3-MYB expression and lead to anthocyanin biosynthesis (Li et al 2018;Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%